Was Freedom Road a Dead End? Political and Socio-Economic Effects of Reconstruction in the American South - Jeffry Frieden; Richard S. Grossman; Daniel Lowery (Center for Economic Studies and ifo Institute (CESifo), 2024)
We investigate how Reconstruction affected Black political participation and socio-economic advancement after the American Civil War. We use the location of federal troops and Freedmen's Bureau offices to indicate more intensive federal enforcement of civil rights. We find greater political empowerment and socio-economic advances by Blacks where Reconstruction was more rigorously enforced and that those effects persisted at least until the early twentieth century, although these advances were weaker in cotton-plantation zones. We suggest a mechanism leading from greater Black political power to higher local property taxes, through to higher levels of Black schooling and greater Black socio-economic achievement.
Keywords: N31; P10; O10; O51; 330; reconstruction; institutions; US Civil War; economic development